Immunohistochemical Detection of 5T4 in Renal Cell Carcinoma. Issue 3 (6th March 2023) - Miller, Christopher P.; Shokri, Farinaz; Akilesh, Shreeram; Xu, Yuexin; Warren, Edus H.; Tykodi, Scott S.; Tretiakova, Maria
Abstract : 5T4 (trophoblast glycoprotein encoded by TPBG ) is a cancer/testis antigen highly expressed in renal cell carcinoma (RCC) and many other cancers but rarely in normal tissues. Interest in developing 5T4 as a prognostic biomarker and direct targeting of 5T4 by emerging receptor-engineered cellular immunotherapies has been hampered by the lack of validated 5T4-specific reagents for immunohistochemistry (IHC). We tested 4 commercially available monoclonal antibodies (mAbs) for the detection of 5T4 in formalin-fixed, paraffin-embedded RCC and normal tissues. Using parental and TPBG -edited A498 cells, 3 mAbs showed 5T4 specificity. Further analyses focused on 2 mAbs with the most robust staining (MBS1750093, Ab134162). IHC on tissue microarrays incorporating 263 renal tumors showed high staining concordance of these 2 mAbs ranging from 0.80 in chromophobe RCC to 0.89 in advanced clear cell RCC (ccRCC). MBS1750093, the most sensitive, exhibited 2+/3+ staining in papillary RCC (92.2%) > advanced ccRCC (60.0%) > chromophobe RCC (43.6%) > localized ccRCC (39.6%) > oncocytoma (22.7%). RNA in situ hybridization also revealed high levels of TPBG RNA were present most frequently in papillary and advanced ccRCC. In advanced ccRCC, there was a trend towards higher 5T4 expression and regional or distant metastases. Normal organ controls showed no or weak staining with the exception of focal moderate staining in kidney glomeruli and distal tubules by IHC. These data identify mAbs suitable for detecting 5T4 in formalin-fixed, paraffin-embedded tissues and demonstrate both interpatient and histologic subtype heterogeneity. Our validated 5T4 IHC protocol will facilitate biomarker studies and support the therapeutic targeting of 5T4.